Hubungan Antara Beban Tas Terhadap Risiko Skoliosis Pada Anak Usia 9-12 Tahun di SDN Gonilan 02 - Zara Sugiyarti; Adnan Faris Naufal (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Many incidents that occur in school-age children are postural errors in carrying out learning activities. One of the causes of posture errors is the use of bags that are too heavy. The weight of a bag that is more than 10% of the child's body weight can affect posture, especially the curves of the spine and is at great risk of causing scoliosis. To determine whether there is a relationship between bag weight and risk of scoliosis in children aged 9-12 years at Gonilan 02 Elementary School. Using the Cross Sectional Study method, with a sample of 110 children using the Total Sampling technique. Based on the results of research that has been conducted from the Spearman’s rho Test, the significance value of p = 0.000 is obtained, which indicates that there is a relationship between the bag load and the risk of scoliosis in children aged 9-12 years at Gonilan 02 Elementary School. The value of r = 0.418 means that the level of closeness of the relationship is moderate and the data is positive, namely the increasing value of the independent variable (bag load), the value of the dependent variable (risk of scoliosis) will also increase. Based on the results of the research that has been done, it shows that there is a relationship between the bag load and the risk of scoliosis in children aged 9-12 years at Gonilan 02 Elementary School. The significance value is p = 0.000. With the level of closeness of the relationship worth r = 0.418, which means that the data is moderate and the data is positive, namely the increasing value of the independent variable (bag load), the value of the dependent variable (risk of scoliosis) will also increase.